Burden of Systemic Lupus Erythematosus on Employment and Work Productivity: Data From a Large Cohort in the Southeastern United States. Issue 6 (June 2014) - Drenkard, Cristina; Bao, Gaobin; Dennis, Greg; Kan, Hong J.; Jhingran, Priti M.; Molta, Charles T.; Lim, S. Sam
<x xml:space="preserve">Abstract</x> Objective To examine the burden of systemic lupus erythematosus (SLE) on work loss, unemployment, and work productivity impairment in an SLE cohort from the southeastern US. Methods We examined 689 SLE patients ages 18–64 years from the Georgians Organized Against Lupus (GOAL) cohort. GOAL is a longitudinal cohort predominantly derived from the Georgia Lupus Registry, a population‐based registry established in metropolitan Atlanta. We used the Kaplan‐Meier method to assess the proportion of patients who self‐reported work loss since diagnosis. We compared unemployment between SLE patients and the general population from the same geographic area, calculating the standardized unemployment ratio (SUR) within demographic and disease strata. We also calculated the percentage of work productivity impairment by disease outcomes. Results Of 511 patients employed at diagnosis, 249 (49%) experienced work loss within an average disease duration of 13 years. The proportion of patients who lost their jobs since diagnosis was almost twice for African Americans than for whites. However, the SURs were similar across demographic characteristics, including race. Patients with severe disease activity and severe organ damage had the highest SUR at 4.4 and 5.6, respectively. Among those that remained employed, patients with severe fatigue, neurocognitive symptoms, and musculoskeletal symptoms had the highest impairment of work productivity. Conclusion SLE imposes a substantial toll on individuals and burden on society. Major factors that negatively impact work outcomes are fatigue, disease activity, and organ damage. More effective treatments along with coping strategies at the workplace are needed to reduce the burden of SLE on work outcomes.